Latin American and Caribbean Petroleum Engineering Conference 1997
DOI: 10.2118/39009-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Displacement Efficiency During Primary Cementing

Abstract: Different philosophies exist for how to design cementing jobs in order to achieve the best possible displacement. This is due to the fact that the process is complex and that it often is difficult to measure the degree of displacement in a well. The trend towards extended reach wells and slim hole wells gives additional challenges when trying to achieve good displacement. A large amount of high quality displacement experiments have been performed in a 4m long laboratory scale loop. Laminar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…by rotation, and this has been addressed by Carrasco-Teja & Frigaard (2009), Carrasco-Teja & Frigaard (2010), Tardy & Bittleston (2016) and Tardy (2018). Three-dimensional simulations of annular displacement flows were first developed in the late 1990s but were too slow for practical usage (Szabo & Hassager 1997;Vefring et al 1997). In recent years interest has revived in these methods as open source and other computational codes have become widely accessible and multi-processor computations have made such calculations manageable at reasonable resolutions over increasingly long annuli and even for non-Newtonian fluids, e.g.…”
Section: Modelling Primary Cementing Flowsmentioning
confidence: 99%
“…by rotation, and this has been addressed by Carrasco-Teja & Frigaard (2009), Carrasco-Teja & Frigaard (2010), Tardy & Bittleston (2016) and Tardy (2018). Three-dimensional simulations of annular displacement flows were first developed in the late 1990s but were too slow for practical usage (Szabo & Hassager 1997;Vefring et al 1997). In recent years interest has revived in these methods as open source and other computational codes have become widely accessible and multi-processor computations have made such calculations manageable at reasonable resolutions over increasingly long annuli and even for non-Newtonian fluids, e.g.…”
Section: Modelling Primary Cementing Flowsmentioning
confidence: 99%
“…Other than the studies by Tehrani and coworkers, there have been only occasional experimental results reported (e.g. Jakobsen et al 1991;Vefring et al 1997;Dutra et al 2004;Nguyen et al 2008).…”
Section: Introductionmentioning
confidence: 99%